Analysis of Speech Acts in COVID-19-Related Facebook Comments - Nor Syamimi Iliani Che Hassan; Nor Hairunnisa Mohammad Nor (Proceedings, 2022)
As one of the most popular social networking sites, people use Facebook to get the latest information related to the COVID-19 pandemic. Driven by this trend and the motivation to address the gap in studies on speech acts on Facebook, we sought to examine Facebook users’ comments about COVID-19 by identifying the speech acts used to communicate users’ thoughts in their comments. These were direct comments posted in response to COVID-19-related posts uploaded by the Malaysian National Security Council on their official Facebook account. Our analysis revealed that five speech acts were used to communicate specific purposes intended for two groups of recipients: the government and citizens.